Structuring Effective 1-1 Support : Technical Guidance Note - Wilichowski, Tracy; Popova, Anna (World Bank, Washington, DC, 2022)
Teachers in low- and middle-income countries often lack the knowledge to improve student achievement and exhibit weak cognitive skills and ineffective teaching practices. Teacher professional development (TPD) programs that are embedded as part of a larger comprehensive capacity development strategy and include ongoing individualized feedback have shown large positive effects on teachers' instruction, and, subsequently, on student learning outcomes. However, what this comprehensive professional development entails in practice has not been systematically documented. The questions are who in the system is best placed to support teachers; how many teachers should these individuals support; how often should these individuals visit teachers; and how long should these individuals observe and provide feedback. This technical guidance note provides explicit guidance for policymakers on how to structure the delivery of a successful in-service TPD coaching intervention. This note also can be used by Task Team Leaders (TTLs) to establish dialogue with their clients and to inform project preparation and supervision.